Demographic Change of Hajam (Thakur) Community in Dhalkebar and Sakhuwa Mahendranagar VDC of Dhanusha District - Thakur, Rajendra (Academic Voices: A Multidisciplinary Journal, 2014)
Nepal is a land of multi-ethnic, multi-religious and Multi lingual country located on the Southern lap of the Himalayas. There are 125 numbers of identified ethnic groups in Nepal.Numerically, the Hajam (Thakur) lies between 33rd ethnic groups. When the people arose on the earth, the Hajam (Thakur) also appeared with them. The term ‘Nai’ (Hajam/Thakur) derived from Sanskrit Language where there is synonymous term ‘Napitah’. According to Navik Puran ‘Nai’ has ben originated from ‘Navik Dev’. From the ancient time they cut Darhi, Moochchha, and Hair, and then only people look smart and attractive in their face. Therefore, Hajam (Thakur) is called the “Symbol of Civilization”. Hajam is also called very faithful person in the world. It is a legendry that God Vishnu gave the birth of ‘Nai’ from his naval. The total population of Hajam / Thakur was 98169 (2001) represents 0.43% and 117758 (2011), represents 0.44% of the total. The total population of Hajam in Dhalkebar was 91 (2001) and 114 (2011) and Sakhuwa Mahendranagar was 126 (2001) and 282 (2011). The main objective of this paper is to deal with ecological condition and population perspectives. This study is based on primary as well as secondary original data, which was collected door to door by every household in the study area. Academic Voices, Vol. 3, No. 1, 2013, Pages 28-32 DOI: http://dx.doi.org/10.3126/av.v3i1.9998